Development of conceptual frameworks for intelligent management of supply and demand in the labor market of information technology specialists - Мамедова, Масума Гусейн кызы; Мамедзаде, Фаик Рамиз оглы (Eastern-European Journal of Enterprise Technologies, 2015)
A comprehensive analysis of the labor market of IT specialists was performed, and conceptual frameworks of intelligent management of the latter were proposed. The concept of «intelligent management of supply and demand in the labor market of IT specialists», which lies in making the best management decisions on minimizing the imbalance between the supply and demand of IT specialists was introduced. The preconditions that underlie the research methodology of the labor market of IT specialists were determined, and the urgency of a systematic approach to individual labor market segments was substantiated. The basic structural components of a conceptual model of the intelligent management of matching supply and demand of IT specialists, determined by the demand for IT personnel through requirements for IT specialized vacancies, supply of IT specialists with a personalized intellectual capital, mechanisms and tools to assess the consistency degree of supply and demand vectors and support for the development processes of control actions for matching supply and demand of IT specialists in the labor market were highlighted. The composition was determined, and generalized model of the intelligent management system of the IT labor market was proposed, a general problem formulation of matching supply and demand of IT specialists was given. The classification of the indicators, features and factors that characterize the supply and demand of IT specialists, based on the author's interpretation of the intelligent human resource management in the IT sector, the specifics of the IT industry, task context and invariant for specialists with various training profiles was carried out. The information model of the dynamics of the aggregate supply in the market of IT specialists, reflecting the inflows and outflows, was proposed. The transactional model of the intelligent management system of the labor market, allowing to describe the interaction of demand and supply vectors of IT specialists in a given time interval and sources of resource flows was designed.